Farmers' Indebtedness and Suicides Impact of Agricultural Trade Liberalisation in Kerala - P D JEROMI (Economic and Political Weekly August 4, 2007, 2007)
The experience of Kerala during the past decade shows how and to what extent a traditional export-oriented agricultural sector in a small local economy can suffer due to trade liberalisation sans any safety nets and comprehensive restructuring programmes. With a decline in exports, rise in imports and a consequent drop in prices, coupled with frequent droughts, stagnant production and productivity, farm income declined drastically and increased the indebtedness of farmers. A sad manifestation of the severity of the situation was the widespread suicides by farmers in the state. This article examines the factors leading to the farm crisis, the rise in indebtedness and various dimensions of farmer suicides.